The family as a space: multilingual repertoires, language practices and lived experiences. Issue 8 (14th September 2021) - Lanza, Elizabeth
ABSTRACT: The field of family language policy has flourished in recent years addressing an ever-increasing breadth of transnational populations, family types, and linguistic configurations. Furthermore, diverse established and innovative methodological approaches have unlatched the door to enhanced understandings of family multilingualism. A focus on ethnographic approaches is in line with current trends in sociolinguistic enquiry, providing deep insight into multilingual families, as demonstrated by this thematic issue on 'Exploring the multilingual family repertoire: Ethnographic approaches', edited by Luk Van Mensel and Maartje De Meulder. An underlying current in the studies of this special issue is the notion of the family as a space, negotiated through the multilingual family repertoire – multilingual practices that embrace the speakers' lived experiences. This concluding discussion analyzes the ways in which the four articles address the family as a multilingual space and highlights some of the more salient aspects that deserve further attention, looking beyond at new potential approaches to critically addressing family multilingualism.